Digitization capacity and skills of academic librarians in Nigeria - Adeleke, Akinniyi A; Senior Librarian (University , Nigeria, 2016)
In order to increase their global visibility and better performance in the web ranking of world universities, more Nigerian universities have been devising creative means of increasing their digital contents in the public domain resulting in more sharability of institutional resources. Digitization builds capacity for the university library system to realize its mandate of supporting learning, teaching and research activities of its parent institutions through the instrumentality of the emerging and evolving information and communications technologies (ICTs). However, certain skill sets and competencies are required by librarians in Nigerian universities to establish and maintain digital collections in their respective institutions. A questionnaire survey is conducted on this category of information professionals in ten selected private and public universities that have minimum ICT infrastructure required for digitization. The collected data are analyzed and results presented in simple descriptive statistics.